If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 9 + 2x + 8 = -4 Reorder the terms: 9 + 8 + X + 2x = -4 Combine like terms: 9 + 8 = 17 17 + X + 2x = -4 Solving 17 + X + 2x = -4 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + X + -17 + 2x = -4 + -17 Reorder the terms: 17 + -17 + X + 2x = -4 + -17 Combine like terms: 17 + -17 = 0 0 + X + 2x = -4 + -17 X + 2x = -4 + -17 Combine like terms: -4 + -17 = -21 X + 2x = -21 Add '-2x' to each side of the equation. X + 2x + -2x = -21 + -2x Combine like terms: 2x + -2x = 0 X + 0 = -21 + -2x X = -21 + -2x Simplifying X = -21 + -2x
| (3.6y+1)/.4=3.3y | | 3(2+5)=2+19 | | (3.6y+1)/04=3.3y | | m+20=80 | | Y^4=400 | | 7x^6=12 | | -2/4/7 | | 2r-36=6r-12 | | 0=4k^2-15k+20 | | -35/-0.875 | | 3(k+1)+2k=13 | | 2x^4=120 | | -7x^2-24x-9=0 | | 3m+4=12 | | p14=-20 | | m+80=140 | | t(25)=0.07(25)^3/2 | | 6x=-18y-12 | | 5x-3=6x-2x | | 0y-5(1+y)=3(2y-2)-20 | | F(x)=(t-1)(t+3) | | 2t-7-52=11 | | 3x-5=7x-49 | | 42=-6g | | 4/9y-3 | | e^5x+8=13 | | -3(1+4.5r)=-17.5 | | 1x^2+4x-6=0 | | v/7=-13 | | 7.4r+9-2r=25.2 | | 7x+7=3-5z | | m=4m+11 |